Propagation of genotype VII Newcastle disease virusin transformed chicken embryo fibroblast cell line - Mohamad Wali, Haryati Shila; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The quest for easy propagation and manipulation of virus steer researchers to explore possibilities of propagating viruses in cell lines. Various types of animal primary cells as well as cell lines have been utilized as an excellent choice for virus cultivation which includes Newcastle disease virus (NDV). Among the cells usually exploited as virus replication host are chicken embryo kidney (CEK), chicken embryo liver (CEL), chicken embryo fibroblast (CEF), African green monkey kidney (Vero), avian myogenic (QM5) and chicken-embryo-related (CER) cells. Therefore, this study is targeted to ascertain the titer of virulent NDV strain IBS002/11 following adaptation on transformed chicken embryo fibroblast cell line (UMNSAH/DF-1). It makes use of the Spearman-Karber calculation which was verified using the HA assay. Genotype VII velogenic NDV strain IBS002/11 was propagated in UMNSAH/DF-1 cells until it reaches 80% confluence. Ten-fold viral serial dilutions were inoculated onto the cells and incubated until cytopathic effects (CPE) was detected. Each dilution was carried out in triplicates. Consequently, supernatant from each well was subjected to HA assay using 0.5 – 1% chicken red blood cells (RBC) and the number of positive results was recorded. Eventually, virus titer as tissue culture infective dose (TCID50) was estimated using the Spearman-Karber formula. CPE was detected as early as 48 h in subsequent viral passages compared to earlier passages (approximately 4 days). Hence, the virus titer also increases with increasing virus passages. NDV strain IBS002/11 was successfully adapted in transformed chicken embryo fibroblast cell line (UMNSAH/DF-1) and titrated for further experiments.